A Critical Response to David Lund’s Argument for Postmortem Survival - Sudduth, Michael (Journal of Scientific Exploration, 2013)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Cambria; mso-fareast-font-family:Cambria; mso-hansi-font-family:Cambria; mso-bidi-font-family:"Times New Roman"; –> <!–[endif] –> <!–StartFragment–> In Persons, Souls and Death, David Lund (2009) presents a cumulative case argument for postmortem survival based on the ostensible explanatory power of survival in relation to data drawn from psychical research. In this paper I argue that the survival hypothesis does not satisfy at least two necessary explanatory criteria accepted and deployed by Lund. First, the data that the survival hypothesis ostensibly explains are not otherwise improbable, as much if not all of the data may be adequately accounted for in terms of psychic functioning among living agents—the LAP hypothesis. Here I argue in considerable detail that Lund’s criticisms of the LAP hypothesis, like those leveled by many other survivalists, are significantly defective. Second, the survival hypothesis does not lead us to expect the data Lund outlines, so it fails with respect to predictive power. Since the “best explanation” is one that leads us to expect what is otherwise improbable, the survival hypothesis i <!–EndFragment–>